2015
DOI: 10.1016/j.enzmictec.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Second generation engineering of transketolase for polar aromatic aldehyde substrates

Abstract: Transketolase has significant industrial potential for the asymmetric synthesis of carboncarbon bonds with new chiral centres. Variants evolved on propanal were found previously with nascent activity on polar aromatic aldehydes 3-formylbenzoic acid (3-FBA), 4-formylbenzoic acid (4-FBA), and 3-hydroxybenzaldehyde (3-HBA), suggesting a potential novel route to analogues of chloramphenicol. Here we evolved improved transketolase activities towards aromatic aldehydes, by saturation mutagenesis of two active-site r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 47 publications
(77 reference statements)
0
36
0
Order By: Relevance
“…14 A particular class of enzymes known as transketolases (EC 2.2.1.1) have been investigated as biocatalytic tools due to their ability to form the asymmetric carbon-carbon bonds commonly required for chemical synthesis of a broad range of pharmaceuticals, agrochemicals, materials, and food ingredients. 15 In nature transketolases require thiamine diphosphate as a cofactor and provide a regulatory function in cellular metabolism, linking the pentose phosphate pathway to glycolysis by catalyzing transfer of a two-carbon fragment from xylulose to ribose sugars, forming heptulose sugars. Biotechnologists have shown that this activity can be exploited to drive an irreversible reaction when providing bhydroxypyruvate (HPA) as the donor of the two-carbon fragment, resulting in carbon dioxide as one of the reaction products.…”
Section: Introductionmentioning
confidence: 99%
“…14 A particular class of enzymes known as transketolases (EC 2.2.1.1) have been investigated as biocatalytic tools due to their ability to form the asymmetric carbon-carbon bonds commonly required for chemical synthesis of a broad range of pharmaceuticals, agrochemicals, materials, and food ingredients. 15 In nature transketolases require thiamine diphosphate as a cofactor and provide a regulatory function in cellular metabolism, linking the pentose phosphate pathway to glycolysis by catalyzing transfer of a two-carbon fragment from xylulose to ribose sugars, forming heptulose sugars. Biotechnologists have shown that this activity can be exploited to drive an irreversible reaction when providing bhydroxypyruvate (HPA) as the donor of the two-carbon fragment, resulting in carbon dioxide as one of the reaction products.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, variants showing improved performance towards propionaldehyde 5a and HPA also improved the catalytic efficiency towards aromatic substrates with HPA, including 3-FBA 7 or 4-FBA [17,18]. For instance, D469T improved the specific activity towards propionaldehyde 5a and HPA by 5-fold and also improved conversion yield of 3-FBA the new library variants had improved activity towards the aromatic aldehyde 3-FBA 7 and pyruvate 2d (Scheme 3).…”
Section: Novel Enzyme Activity Towards 3-fba and Pyruvatementioning
confidence: 75%
“…Addition of the mutation S385Y into the double mutant D469T/R520Q previously improved the catalytic efficiency towards 3-FBA 7 and HPA by significantly decreasing the Km [18]. We therefore introduced the S385Y mutation into the two mutants 4M/D469T/H473N and 4M/D469T/H473N/R520Q to test whether their activities could be improved.…”
Section: Novel Enzyme Activity Towards 3-fba and Pyruvatementioning
confidence: 99%
See 1 more Smart Citation
“…[18,19] In the past ten years many variants of EcTK, GstTK, and Saccharomyces cerevisiae transketolase (ScTK) were createdb y active site targeted directede volution to enhancet he activity for the above mentioned non-phosphorylated substrates. [17,[20][21][22][23][24][25][26][27][28][29][30] Amongt hem also variantsw ith enhanced or reverseds tereoselectivity wered escribed. For details see SI Ta ble S1.…”
Section: Introductionmentioning
confidence: 99%